2022
DOI: 10.2478/jtim-2021-0032
|View full text |Cite
|
Sign up to set email alerts
|

TCDD-inducible poly (ADP-ribose) polymerase promotes adipogenesis of both brown and white preadipocytes

Abstract: Background TCDD-inducible poly (ADP-ribose) polymerase (TiPARP) is a DNA repair enzyme with functions in energy metabolism, signal transduction, cell differentiation, and other biological processes, which may closely related to lipid metabolism and is highly expressed in adipose tissue. Adipose tissue can be divided into white adipose tissue (WAT) that stores energy and brown adipose tissue (BAT) that releases energy and generates heat. In the present study, we investigated whether TiPARP can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Thus, numerous excellent studies that identified BC molecular subtypes have shed new light on BC precision medicine (3)(4)(5). Previous studies have revealed that DDR are complex biological processes, and it is well known that DDR pathways involve in the onset, progression, and therapeutic response of many diseases (6,43). Besides, treatment strategies that target altered DDR function are gradually coming to fruition.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, numerous excellent studies that identified BC molecular subtypes have shed new light on BC precision medicine (3)(4)(5). Previous studies have revealed that DDR are complex biological processes, and it is well known that DDR pathways involve in the onset, progression, and therapeutic response of many diseases (6,43). Besides, treatment strategies that target altered DDR function are gradually coming to fruition.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 , 12 ] Lipidomics is a useful method of studying lipid metabolism under physiological and pathological conditions. [ 13 , 14 ] But to date, studies of the effects of exercise on lipid metabolism have mainly focused on the effects of acute or high-intensity exercise in adults or in individuals with specific diseases [ 7 , 9 , 11 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] . Nieman et al .…”
Section: Introductionmentioning
confidence: 99%